The Rover Boys winning a fortune; or, Strenuous days ashore and afloat - Stratemeyer, Edward, 1862-1930; Rogers, Walter S. (Walter Stanton), 1870-1937 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Rover Boys Winning a Fortune; or, Strenuous Days Ashore and Afloat" by Arthur M. Winfield is a children's adventure novel written in the early 20th century. The narrative follows the Rover boys$1 (BJack, Fred, and their spirited cousins$1 (Bas they navigate youthful escapades, including a pivotal horse race and interactions with old friends and rivals. The book captures themes of camaraderie, competition, and the excitement of coming-of-age experiences. The opening of the story introduces us to Fred Rover, who is hiding a secret that spurs a playful chase among his cousins at the family's old farmhouse. As the boys pursue Fred, they engage in banter that reveals their personalities and dynamics, setting a light-hearted tone for the adventure to come. The stage is set for a race involving Jack Rover against Joe Sedley, a neighbor, which promises excitement and rivalry, especially with the stakes of friendship and reputation at play. Alongside the competitive spirit, the plot hints at deeper tensions with old foes, ensuring readers are left curious about the challenges that lie ahead for the Rover boys. (This is an automatically generated summary.)s
Release date is 2022-12-03
Donald Cummings and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Sea stories; Detective and mystery stories; Treasure troves -- Juvenile fiction; Mexico, Gulf of -- Juvenile fiction; Securities industry -- Juvenile fiction